2018
DOI: 10.1152/japplphysiol.01018.2017
|View full text |Cite
|
Sign up to set email alerts
|

Linalyl acetate restores endothelial dysfunction and hemodynamic alterations in diabetic rats exposed to chronic immobilization stress

Abstract: Although stress is one of the risk factors of diabetes, few studies have assessed the effects of stress on diabetic rats. This study, therefore, analyzed differences in cardiovascular-related factors among control, nonstressed diabetic, and stressed diabetic rats as well as assessed the effects of linalyl acetate (LA) on stressed diabetic rats. Male Sprague-Dawley rats were subjected to immobilization stress throughout the experimental period, and diabetes was induced on day 15 by a single injection of strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…The purpose of this study is to explore the pathogenesis of depression and the effect of Xiaoyaosan on the tryptophan metabolism, which was responsible for the increase in the synthesis and function of 5-HT. Immobilization stress, as a significant stress measure, has been widely applied in various animal experiments 26,27. The CIS-induced model, to a certain extent, simulates the state of depression in clinic 28,29.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study is to explore the pathogenesis of depression and the effect of Xiaoyaosan on the tryptophan metabolism, which was responsible for the increase in the synthesis and function of 5-HT. Immobilization stress, as a significant stress measure, has been widely applied in various animal experiments 26,27. The CIS-induced model, to a certain extent, simulates the state of depression in clinic 28,29.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatments to prevent or reverse muscle atrophy have focused on IGF-1-associated muscle anabolic pathways [35]. Vasodilation following linalyl acetate associated maintenance of vascular endothelium supports results showing that linalyl acetate preserves normotensive levels of diastolic and systolic BP [20]. Linalyl acetate has also been shown to regulate intracellular Ca 2+ levels in vascular endothelial cells and smooth muscle cells, suggesting that the antihypertensive effects of linalyl acetate are associated with vasomotor enhancement [36].…”
Section: Discussionmentioning
confidence: 68%
“…In addition, lavender oil has possibility of preventing cardiovascular disease based on anti-diabetic [14] and antithrombotic activities [15]. Linalyl acetate, a volatile and low toxicity compound contained in citrus fruits, is the main component of lavender oil [16] Linalyl acetate has shown anti-in ammatory effects in vitro [17] and in vivo [18], as well as anti-hypertensive [19], anti-diabetic [20] and anti-stress [21] effects with the ability to prevent vascular endothelium dysfunction [18]. These pharmacological properties suggested that lavender and linalyl acetate could have preventive effects in our rat model of RA with chronic nicotine-induced HTN.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that diabetic animals exposed to chronic stress showed a reduction in endothelial function, changes in SBP and HR. LA (100 mg/kg) was able to revert these parameters to close to control values [87].…”
Section: Linalyl Acetatementioning
confidence: 89%